2018
DOI: 10.1002/hyp.13157
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic and stream flow influences on large wood dynamics and displacement lengths in high gradient mountain streams (Chile)

Abstract: Understanding large wood (LW; ≥1 m long and ≥10 cm in diameter) dynamics in rivers is critical for many disciplines including those assessing flood hazard and risk. However, our understanding of wood entrainment and deposition is still limited, mainly because of the lack of long‐term monitoring of wood‐related processes. The dataset presented here was obtained from more than 8 years of monitoring of 1,264 tagged wood pieces placed in 4 low‐order streams of the Chilean mountain ranges and was used to further ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 74 publications
(159 reference statements)
4
20
1
Order By: Relevance
“…Likewise, we also recorded a significant annual wood exchange, but the total amount of wood underwent a significant change throughout the monitored period at the same time. Consistent with Tonon et al 2018and Iroumé et al (2018), we showed that mobilization and deposition of LW also occur during low-flow conditions below the bankfull stage. Downs and Simon (2001) documented accelerated LW input due to bank instability caused by knickpoint migration and channel incision.…”
Section: Large Wood Load and Transport In A Flood-free Periodsupporting
confidence: 93%
“…Likewise, we also recorded a significant annual wood exchange, but the total amount of wood underwent a significant change throughout the monitored period at the same time. Consistent with Tonon et al 2018and Iroumé et al (2018), we showed that mobilization and deposition of LW also occur during low-flow conditions below the bankfull stage. Downs and Simon (2001) documented accelerated LW input due to bank instability caused by knickpoint migration and channel incision.…”
Section: Large Wood Load and Transport In A Flood-free Periodsupporting
confidence: 93%
“…The presence of roots or the size distribution of supplied wood are controlling wood motion and deposition as well. Logs with roots were less mobile (both in the flume and in the numerical simulations) and traveled significantly shorter distances than logs without roots in agreement with previous studies (Abbe & Montgomery, 1996;Braudrick & Grant, 2000;Cadol & Wohl, 2010;Iroumé et al, 2018;Welber et al, 2013). According to the observations made during the flume experiments, we observe that logs with roots aligned parallel to the flow with their rootwads located upstream were, in some cases, slowly pushed downstream by the drag force exerted on the rootwad, but that the rootwad prevented logs from rolling and, therefore, limited their mobility (Welber et al, 2013).…”
Section: Water Resources Researchsupporting
confidence: 90%
“…Studies of the geomorphic and ecological functions of large wood may come next (Montgomery et al, 2003). Ultimately, short-term studies may evolve into long-term programmes (e.g., Wohl and Goode, 2008;Iroumé et al, 2015Iroumé et al, , 2018aIroumé et al, , 2018b. Such studies can make important contributions in terms of direct observation of gradual processes and infrequent events, which are an important part of large wood dynamics.…”
Section: Growth Of the Fieldmentioning
confidence: 99%